Beyond NMR Spectra of Antimicrobial Peptides: Dynamical Images at Atomic Resolution and Functional Insights - Ramamoorthy, Ayyalusamy (2009)
There is a considerable current interest in understanding the function of antimicrobial peptides for the development of potent novel antibiotic compounds with a very high selectivity. Since their interaction with the cell membrane is the major driving force for their function, solid-state NMR spectroscopy is the unique method of choice to study these insoluble, noncrystalline, membrane-peptide complexes. Here I discuss solid-state NMR studies of antimicrobial peptides that have reported high-resolution structure, dynamics, orientation, and oligomeric states of antimicrobial peptides in a membrane environment, and also address important questions about the mechanism of action at atomic-level resolution. Increasing number of solid-state NMR applications to antimicrobial peptides are expected in the near future, as these compounds are promising candidates to overcome ever-increasing antibiotic resistance problem and are well-suited for the development and applications of solid-state NMR techniques.